KESULITAN BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN DARING SELAMA MASA PANDEMI DI SMAN 1 TEMPURAN - Rahmawati Susanti; Etika Dyah Puspitasari (FKIP Universitas Tanjungpura, 2022)
Online learning is a big challenge for teachers and students, this is because teachers cannot see the learning process directly and students have learning difficulties. In addition, students cannot understand the material that has been delivered by the teacher online. This study aims to determine the causes of student learning difficulties in online learning and to determine efforts to overcome student learning difficulties in biology subjects.This research is a descriptive research. The subjects of this study were students who had learning difficulties and the biology teacher of class XI IPA SMAN 1 Tempuran with the object of this research being students who had learning difficulties during online learning. The sample used is class XI IPA with a population of 176 students. Data collection techniques using a questionnaire through the google form platform and interviews. Data analysis was carried out quantitatively and qualitatively.The results of data analysis showed that internal motivation indicators caused students' learning difficulties in understanding biology subjects during online learning, which was 75%. On external factors, social indicators cause students' learning difficulties in understanding biology subjects during online learning, which is 65%. Efforts to overcome students' learning difficulties do group study and independent study.